Bronchoscopy in Rural Areas? - Reidar Berntsen; Erik Waage Nielsen (Pulmonary Medicine)
Quality of bronchoscopy performed by one single pulmonologist in a scarcely populated subarctic area was compared to the guidelines provided by the British Thoracic Society (BTS). 103 patients underwent bronchoscopy. Diagnostic yield was increased to 76.6% when the first bronchoscopy was supplemented by bronchial washing fluid and brush cytology and to 86.7% (BTS guidelines >80%) after a second bronchoscopy. Median time from referral to bronchoscopy was 10 days and 8 days from positive bronchoscopy to operative referral to another hospital. 1% of patients that underwent transbronchial lung biopsy had minor complications. One pulmonologist had rate of correct diagnosis based on visible endobronchial tumors that was comparable to the rates of numerous pulmonologists at larger centers performing the same procedure. Time delay was short. Rate of complications was comparable. Bronchoscopy performed by one pulmonologist alone could, in organized settings, be carried out at local hospitals in areas of scattered settlement.